Literacy for a learning society: a collective effort with broader vision needed - Nath, Samir Ranjan; Ahmed, Manzoor; Ahmed, Kazi Saleh (BRAC Research and Evaluation Division (RED), 2019)
Based on the application of a purposefully designed test of literacy skills on a nationwide sample, the Education Watch established a benchmark for the literacy situation of the population 11 years and above in Bangladesh. Over a hundred investigators, half of them women, collected data and administered literacy tests on 13,145 people from 3,840 households in 268 rural and urban communities in all 64 districts in October and November 2002. Statistically valid and reliable estimates were made of literacy rates for the population 11 years and above and 15 years and above, as well as, separately for females and males, urban metropolitan centres and municipal areas, and rural areas of six divisions. The policy implications of the findings are also presented at the end. It is expected that the findings of this Education Watch would end the prevailing confusion about the literacy status of the population in the country and serve as the baseline for future planning and assessment of progress in literacy, non formal education and lifelong education.